A angústia como disposição afetiva em Ser e tempo - Soares, Marcelo José (2010)
This study has as objective to investigate the approach of Martin Heidegger on ontological foundations of a phenomenology of affects. For this, to limit the interpretation to the period from 1927 to 1930, specifically in the works Being and Time , What is metaphysics? and Fundamental Concepts of Metaphysics: World, finitude, solitude . From the reconstruction of the general theory of affective measures in Being and Time , seeking to prove the privilege of the provisions of anxiety and boredom and their modes of openness. We will argue that, based on the structures derived from the existing analytical human faced immediately with a fundamental existential structures to be the be-there, namely the affective disposition [Befindlichkeit]. For Heidegger the affective disposition is an ontological structure that is open and the world, while the states of specific mood [Stimmung] are embodiments of the ontic disposition that pervade the world. Further evidence of the crucial role played by anxiety, noting that this sentiment is not enough to be there be-delivered the very existence, but has an obligation to answer for that. Finally we discuss the boredom in their respective ways culminating in an attempt to understand the essence of 'profound boredom' in its primacy.